Can farmland ownership confirmation promote farmers’ adoption of conservation tillage techniques: empirical evidence from the Yellow River Basin in China - Liu, Zongfei; Yan, Qianqian (Frontiers in Sustainable Food Systems, 2025)
IntroductionCultivated land is the basic resource for human survival, and the quality of arable land affects the level of food supply. Previous studies have shown that farmland ownership confirmation will promote farmers’ cultivated land quality protection behaviour, but it is unclear whether it will promote farmers’ choice of conservation tillage techniques.MethodsThis paper uses sample data of farmers in the Yellow River Basin in China’s key agricultural regions to analyse the impact of the new round of farmland tenure confirmation on farmers’ choice of conservation tillage techniques.ResultsThe results show that farmland ownership confirmation can significantly promote the adoption of conservation tillage technology by farmers. Resource allocation plays a significant intermediary role in the impact of farmland ownership confirmation on farmers’ adoption of conservation tillage techniques. The study found that farmers with different family situations have different levels of adoption of conservation tillage technology after farmland ownership is confirmed. Farmers with higher education levels, smaller arable land areas, and less arable land are more likely to adopt those techniques. This study shows that the new round of farmland title confirmation has had a positive effect on the spread and application of agricultural technology in rural areas.DiscussionFurther improving the farmland ownership policy can not only improve the efficiency of agricultural production, but also promote the sustainable development of agriculture, which is of great research significance for guaranteeing national food security.